1986
DOI: 10.1021/bi00367a060
|View full text |Cite
|
Sign up to set email alerts
|

Processivity of T4 endonuclease V is sensitive to sodium chloride concentration

Abstract: We previously reported that endonuclease V of bacteriophage T4 reacts processively with pyrimidine dimers in UV-irradiated DNA, tending to react with all of the dimers on one DNA molecule before reacting with any dimers on another DNA molecule [Lloyd, R. S., Hanawalt, P. C., & Dodson, M. L. (1980) Nucleic Acids Res. 8, 5113-5127]. In this paper we show that this processivity depends upon salt concentration: it can be detected in 10 mM NaCl but not, by our methods, in 100 mM NaCl. In addition, we show that endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 20 publications
(26 reference statements)
2
38
0
Order By: Relevance
“…A number of proteins involved in DNA repair have been shown to act processively. These include DNA helicases [10], T4 endonuclease V [11,12], Micrococcus luteus UV endonuclease [13], UvrABC nuclease [14], DNA glycosylases [15,16], and AP endonucleases [17].…”
mentioning
confidence: 99%
“…A number of proteins involved in DNA repair have been shown to act processively. These include DNA helicases [10], T4 endonuclease V [11,12], Micrococcus luteus UV endonuclease [13], UvrABC nuclease [14], DNA glycosylases [15,16], and AP endonucleases [17].…”
mentioning
confidence: 99%
“…Apparently, the W128S mutation is more pronounced at 10 mM than at 100 mM salt concentration. One interpretation of these results is that tryptophan-128 is involved in DNA processivity which is somehow functionally coupled to the nicking activity ofthe AP lyase activity since both these processes are more evident at lower salt concentrations (36,37). An oligonucleotide with a single abasic site may not clearly distinguish the defect of W128S if this mutation involves DNA processivity.…”
Section: Resultsmentioning
confidence: 94%
“…One possible explanation for these discrepancies may be the conditions for assaying endonuclease V activity. Lantham et al (24) used salt concentrations of 100mM which favors a distributive action of the enzyme (36,37) and which suppresses the AP lyase activity (5). At low salt concentrations (10 mM), which was used in our study and in several previous studies (3,5), the AP lyase is stimulated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to effectively map the DNA repair domain in the DHFR region in CHO cells by analysis of the efficiency of pyrimidine dimer removal from a series of overlapping restriction fragments, 7 to 30 kb in length, which spanned the entire gene and its surrounding sequences (19). We found that within 8 hr after a UV dose of 20 J/m2, the cells had removed more than 40% (20,21).…”
Section: Introductionmentioning
confidence: 82%